Interdependence of oxidative/antioxidant system indicators and thyroid status under conditions of prolonged exposure to small doses of radiation - Sokolenko, V. L.; Sokolenko, S. V. (Regulatory Mechanisms in Biosystems, 2019)
We have studied the interdependence of the intensity of oxidative processes/antioxidant level and the thyroid status parameters in a group of students aged 18–24 who lived for a long time in the territory of enhanced radioecological control (density of soil contamination by isotopes (137Cs 3.7 ∙ 104 – 18.5 ∙ 104 Bq/m2). We examined 50 people from relatively environmentally friendly areas (control group) and 50 people from IV radiation zone (experimental group). In the experimental group, there were no individuals with clinical manifestations of thyroid pathology. However, subgroups with signs of hyperthyroidism and hypothyroidism were identified. We evaluated the level of cortisol, thyrotrophic hormone (TSH), triiodothyronine (T3), thyroxine (T4), malonic dialdehyde (MDA), ceruloplasmin (CP), transferrin (Tf), sulfhydryl groups (SH); we calculated the oxidative stress index (OSI). The research was conducted one month before the examination time and also during the exams as a factor in increased emotional stress. A lowered CP level was found in the subgroup with signs of hypothyroidism; SH groups – in all subgroups, separated by thyroid status. The oxidative stress index was higher in all students examined of the experimental group, compared with the control. The growth of MDA level is marked in the experimental group – it is the most strongly pronounced in conditions of additional emotional load in people with signs of hyperthyroidism and hypothyroidism. CP level significantly decreased in the subgroup of hyperthyroidism on the background of T3 decrease. OSI increased in all students examined from the experimental group. In the subgroup of hypothyroidism it became significantly higher than in the subgroup of euthyroidism. A positive correlation between the levels of CP and T3 was found. The highest values of the correlation coefficients were noted for subgroups with signs of hyperthyroidism and hypothyroidism, with the coefficient significance increasing under conditions of emotional stress. The index of oxidative stress in the experimental group positively correlated with the level of TSH – in terms of emotional stress, the statistical significance of the coefficients disappeared. In the subgroups divided by thyroid status, variability of interactions between OSI and T3 was observed but it was not statistically significant. It was found that the participation of thyroid status in supporting redox homeostasis in people aged 18–24 who suffered from chronic small-doze radiation exposure was realized mainly by the influence on the antioxidant system. The ability of thyroid hormones to maintain a proper antioxidant state was suppressed in this group. The unbalanced relationship between thyroid hormones and oxidative stress indicators is strongly manifested under conditions of additional emotional stress.